Codimension-one bifurcation analysis and chaos of a discrete prey–predator system - Abdul Qadeer Khan; Syeda Noor-ul-Huda Naqvi (Journal of Taibah University for Science)
In this paper, we explore local dynamics at equilibrium points, the existence of bifurcation sets and codimension-one bifurcation analysis of a discrete prey–predator system with Holling type-II functional response. Further, OGY and Hybrid control strategies are utilized to control chaos in the under study discrete model due to the occurrence of Neimark–Sacker and flip bifurcations. Finally, numerical simulations are given to verify theoretical results.